Evaluation of Rowing Sport Coaching Program in PODSI Barito Kuala Regency - Hadi, Supian; Rahmadi, Rahmadi; Mashud, Mashud (UNIVERSITAS NEGERI MAKASSAR, 2021)
The research objective was to determine whether the coaching program at PODSI Barito Kuala Regency was effective and following what was made in the coaching program. This type of research is an evaluation of the Countenance Stake model. Data collection was done by filling out questionnaires, interviews, observation and documentation. The results of the research with the evaluation of the Contenance Stake model from filling out the questionnaire showed that the antecedent component was obtained in the medium category, the transaction component was in the medium category, and the outcome component was in the moderate category, the results of interviews, observation and documentation of PODSI Barito Kuala Regency, in collaboration with the Provincial Dispora and Kemenpora in the form of PPLP and PPLPD, do not have a licensed rowing coaching coach, do not have a licensed referee, the facilities are still lacking. The program research recommendation is continued to need to increase the capacity of coaches, referees and improve facilities, infrastructure and special canals for rowing so that they become a medium for recreation for athletes and the implementation of rowing championships in the Barito Kuala district.